Anaerobic Digestion in Built Environments - Sikora, Anna (IntechOpen, 2021)
Anaerobic digestion of biomass to biogas, commonly occurring in natural anoxic ecosystems, is an excellent method for utilizing wastes and producing green energy. This book presents examples of local installations of AD, or their proposals, located at small factories, workplaces, and in rural areas and housing complexes. The facilities consider the specific nature of the region, site conditions, and specificity of the utilized wastes. They protect the environment and ensure dispersed energy production. The latter is of great economic significance due to its closeness to end customers. Small local installations expand the pool of renewable energy on a global scale.